2022
DOI: 10.3390/su14020791
|View full text |Cite
|
Sign up to set email alerts
|

Cryosphere Services to Support SDGs in High Mountains

Abstract: The cryosphere is able to provide a variety of services for the benefit of human well-being and underpins regional sustainable development. The cryosphere deterioration induced by climate change is impacting the services and will subsequently impede the efforts to meet sustainable development goals (SDGs) in high mountain societies. Here, we detail the context of cryosphere services and establish a dataset for its linkage to SDGs. This allows us to uncover its roles in supporting SDGs, directly by a causal con… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 52 publications
0
7
0
Order By: Relevance
“…Cultural and spiritual tourism centred on people, places, and events can be marketed as niche high-mountain tourism products in the international tourism market and would contribute significantly to economic and social development goals (Haq & Medhekar, 2020). Along with cultural and spiritual tourism, adventure tourism (winter sports, mountaineering, and trekking) is a major attraction related to the cryosphere (MoCTCA, 2020;Shijin et al, 2020;Zhang et al, 2022).…”
Section: Tourismmentioning
confidence: 99%
“…Cultural and spiritual tourism centred on people, places, and events can be marketed as niche high-mountain tourism products in the international tourism market and would contribute significantly to economic and social development goals (Haq & Medhekar, 2020). Along with cultural and spiritual tourism, adventure tourism (winter sports, mountaineering, and trekking) is a major attraction related to the cryosphere (MoCTCA, 2020;Shijin et al, 2020;Zhang et al, 2022).…”
Section: Tourismmentioning
confidence: 99%
“…The cryosphere services, encompassing four categories and 12 types, are applied to establish the relationship with 15 SDGs and 62 targets in total. It includes provisioning (freshwater, clean energy, ice and snow material), regulating (climate, runoff, environment, and hydrothermal regulation), cultural (aesthetic and recreational, research and education, religion, spirit, and cultural), and supporting services (habitation, infrastructure and engineering) [17].…”
Section: Data and Materialsmentioning
confidence: 99%
“…The extensive linkage between cryosphere services and SDGs indicate that the cryosphere is irreplaceable in sustainable development in high mountains [16]. Overall, 62 of 167 targets in SDGs are affected directly or indirectly by the cryosphere services [17]. The cryosphere services are also considered to be essential in the process that transforms cryospheric resources to the benefit that societies can obtain [2,18].…”
Section: Introductionmentioning
confidence: 99%
“…Food provision, water provision, carbon storage, and habitat & biodiversity were recognized as critical services contributing to >14 SDG targets, especially in SDG6 (Clean Water and Sanitation), SDG13 (Climate Action), SDG14 (Life Below Water), and SDG15 (Life on Land) (Wood et al, 2018;Yang et al, 2020). Water provision, water regulation, climate regulation and research & education among the cryosphere services were found to have strong contributions to SDG1 (No Poverty), SDG 2 (Zero Hunger), SDG 6 (Clean Water), SDG11 (Sustainable Cities and Communities), SDG12 (Responsible Production and Consumption) and SDG15 (Life on Land) (Zhang et al, 2022a). Different types of ESs contribute different amounts to SDGs.…”
Section: Introductionmentioning
confidence: 99%
“…Online surveys that gather expert views on the importance of ESs to achieving the SDGs were conducted to evaluate the strengths of the SDG-ES relations (Wood et al, 2018;Yang et al, 2020). Network analysis was used to unravel the relationship between cryosphere services and SDGs based on the chain of causal effects and cascading effects (Zhang et al, 2022a). Additionally, bibliometric network analysis was also applied to explore the connections between ESs and SDGs (Hawken et al, 2021).…”
Section: Introductionmentioning
confidence: 99%